Source modification for efficiency enhancement of marine controlled-source electromagnetic method - Rostami, A. (Oxford University Press, 2021)
Controlled-source electromagnetics is a strongly efficient technique to explore deep-water marine hydrocarbon reservoirs. However, the shallow-water unsolved limitations of electromagnetic shooting methods still exist. In this regard, this work aims to alter the existing conventional electromagnetic source such that it can converge the down-going electromagnetic wave while simultaneously dispersing the up-going electromagnetic energy to minimise the airwave in shallow water. This work presents computed electric current distribution inside a modified transmitter, using a method of moments. Simulation and an experiment-based methodology are applied to this work. Finite element simulation of the response of the modified transmitter displayed the capability of the new transmitter in dispersing the airwave, by 15. The experimental setup confirmed a better performance of the new transmitter, showing hydrocarbon delineation of up to 48, compared to the existing conventional transmitter, with 25 oil delineation at the same depths in the same environment. Modification of the electromagnetic source to unbalance the up-down signals may have the potential to enhance the delineation magnitude of the target signal and, as a result, significantly improve oil detection capability. Â© 2021 The Author(s) 2021. Published by Oxford University Press on behalf of the Sinopec Geophysical Research Institute.